Diagnostic utility of small fiber analysis in skin biopsies from children with chronic pain - Görlach, Jonas; Ziegler, Andreas (Muscle & nerve, 2020)
Introduction: Small fiber neuropathies (SFN) are associated with a reduction in quality of life. In adults, epidermal nerve fiber density (END) analysis is recommended for the diagnosis of SFN. In children, END assessment is not often performed. We analyzed small nerve fiber innervation to elucidate the potential diagnostic role of skin biopsies in young patients with pain. Methods: Epidermal nerve fiber density and sudomotor neurite density (SND) were assessed in skin biopsies from 26 patients aged 7 to 20 years (15 female patients) with unexplained chronic pain. The results were compared with clinical data. Results: Epidermal nerve fiber density was abnormal in 50% and borderline in 35% of patients. An underlying medical condition was found in 42% of patients, including metabolic, autoimmune, and genetic disorders. Discussion: Reduction of epidermal nerve fibers can be associated with treatable conditions. Therefore, the analysis of END in children with pain may help to uncover a possible cause and guide potential treatment options.
First published: 20 November 2019
Gesehen am 20.02.2020